Experimental and computational evidence for stabilising parallel, offset π[C(=O)N(H)N=C]⋯π(phenyl) interactions in acetohydrazide derivatives - Tan, Sang Loon *; Cardoso, Laura N. F.; Souza, Marcus V. N. de; Wardell, Solange M. S. V.; Wardell, James L.; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2022)
Parallel, off-set π[C(=O)N(H)N=C] …π(phenyl) interactions are observed in the crystal of (2-thienyl)CH2CON(H)-N=C(H)Ph, along with more conventional non-covalent interactions. All notable interactions have been analysed by the calculated Hirshfeld surfaces, NCI plots and QTAIM analysis. The π[C(=O)N(H)N=C]…π(phenyl) interactions, whereby the N(H) atom lies over the ring centroid and with the N and C atoms on either side of the N(H) atom closely overlay 1,3-carbon atoms of the phenyl ring, are shown to be attractive. Theory suggests the energy of association provided the π[C(=O)N(H)N=C]…π(phenyl) interaction to the molecular packing to be about 15 kJ/mol, a value similar to that provided by similarly orientated benzene 2 and pyridine rings. A survey of the literature of related structures suggests comparable interactions occur in approximately 5-6% of crystals where they can potentially occur.